Residual aggregates in platelet products: what do we know? - Ringwald, J.; Antoon, M.; Eckstein, Reinhold; Cardoso, M. (Vox Sanguinis, 2014)
Platelet (PLT) aggregates can occur during or after PLT component processing. However, very few reports investigating the phenomenon and its clinical significance have been published. In this review, currently available information about aggregates in PLT products is summarized and possible causal factors as well as preventive strategies are discussed.A review of the MEDLINE® database for relevant publications from 1960 to May 2013 was conducted.It is well known that PLT aggregates may occur during or after the PLT product preparation process. These aggregates normally dissipate with rest and agitation. However, in some rare cases, the aggregates do not dissipate within 24 h and can persist up to the end of storage. Exposure to low temperature, low pH, short resting period after collection, different collection systems, presence of bubbles or foam inside the PLT bag, PLT-container interactions, proper product mixing and donor-dependent variables may have an impact on the formation of PLT aggregates. Although publications are rare, the presence of small numbers of PLT aggregates appears to have only limited impact on PLT in vitro quality. Furthermore, data on the clinical impact of PLT aggregates are lacking.Despite the fact that PLT aggregates occur in PLT products, published data on this topic remain scant. Considering the concern of clinicians about this phenomenon, more studies are needed which should focus on the possible clinical impact of such aggregates and precautions to avoid PLT aggregate formation in PLT products.
EVALuna2:15971